Janasa, new variety of Azufrado type beans for the state of Sinaloa, Mexico - Salinas Pérez, Rafael Atanasio; Rodríguez Cota, Franklin Gerardo; Padilla Valenzuela, Isidoro; Valencia Martínez, Yeny; Ortiz Cano, Héctor Genaro; Acosta Gallegos, Jorge Alberto (Revista Mexicana de Ciencias Agrícolas, 2018)
In Sinaloa, the yellow-grained bean of the type Azufrado- Peruvian, Nueva Granada breed, particularly the variety Azufrado Higuera, has the greatest area planted with this legume. In this article, we describe the development and the agronomic characteristics of a new variety of this type of bean, “Janasa”, which will help broaden the number of varieties available in this commercial class. This new variety was developed from the breeding of three lines between ((Azufrado Pimono-78 / Canario-72) // AZPA- 5). The development of the selection was based on the tolerance to viral (BGMV, BCMV and BCMNV) and fungal diseases such as (Sclerotinia sclerotorium) and rust (Uromyces appendiculatus var. appendiculatus). The Janasa plant has determined habit type I, it is 44 cm tall, it reaches physiological maturity in 104 days and the weight it has for 100 seeds varies between 42 and 44 g. Janasa presents adaptation in the bean-producing areas in northern Sinaloa in irrigation conditions, where it has presented high yield potential and tolerance to diseases during the autumn-winter cycle, surpassing the yield of the variety Azufrado Higuera with an average of 322 kg ha-1 in four years.